2011
DOI: 10.1001/jama.2011.1277
|View full text |Cite
|
Sign up to set email alerts
|

Graduated Driver Licensing and Fatal Crashes Involving 16- to 19-Year-Old Drivers

Abstract: In the United States, stronger GDL programs with restrictions on nighttime driving as well as allowed passengers, relative to programs with none of the key GDL elements, were associated with substantially lower fatal crash incidence for 16-year-old drivers but somewhat higher fatal crash incidence for 18-year-old drivers. Future studies should seek to determine what accounts for the increase among 18-year-old drivers and whether refinements in GDL programs can reduce this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 38 publications
(34 reference statements)
4
65
1
1
Order By: Relevance
“…In general, the literature on the effects of MLDA changes on fatal/nonfatal MVCs in youth populations has found that raising the MLDA was associated with decreases, and lowering the MLDA was associated with increases. 20,[22][23][24][25][26][27][28] Many of these studies, however, are decades old and it would be reasonable to argue that the impacts of MLDA observed in the 1970s and 1980s might be substantially attenuated in the contemporary context, owing in large part to advances in both traffic safety and alcohol policy (e.g., road and vehicle safety, 29,30 graduated driver licensing legislation, [31][32][33][34] and impaired-driving laws [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the literature on the effects of MLDA changes on fatal/nonfatal MVCs in youth populations has found that raising the MLDA was associated with decreases, and lowering the MLDA was associated with increases. 20,[22][23][24][25][26][27][28] Many of these studies, however, are decades old and it would be reasonable to argue that the impacts of MLDA observed in the 1970s and 1980s might be substantially attenuated in the contemporary context, owing in large part to advances in both traffic safety and alcohol policy (e.g., road and vehicle safety, 29,30 graduated driver licensing legislation, [31][32][33][34] and impaired-driving laws [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…16 By the end of 2000, all but nine states had GDL laws and others have additional requirements that place restrictions on unsupervised driving (Masten, Foss, and Marshall, 2011.) The motivation for these laws is not so much to restrict youth driving as it is to improve safety.…”
Section: Other Shifts May Be the Results Of Restrictions Or Constraintmentioning
confidence: 99%
“…: interdiction de conduire entre minuit et 5 h du matin) ; 2) l'interdiction de jeunes passagers ; 3) l'obligation d'une période minimale d'apprentissage de six mois 4) un âge minimal avant d'obtenir le permis régulier (p. ex. : 17 ans) ; et 5) l'obligation de suivre des cours lors de la période d'apprentissage (Dee, Grabowski et Morrisey, 2005 ;Masten, Foss et Marshall, 2011 ;Vanlaar et al, 2009 ;Williams, 2007 ;Williams et Shults, 2010).…”
Section: Les Programmes D'accès Graduel à La Conduiteunclassified